Consistency of MGEX Orbit and Clock Products. (August 2020) - Steigenberger, Peter; Montenbruck, Oliver
Abstract: The analysis centers of the Multi-GNSS Pilot Project of the International GNSS Service provide orbit and clock products for the global navigation satellite systems (GNSSs) Global Positioning System (GPS), GLONASS, Galileo, and BeiDou, as well as for the Japanese regional Quasi-Zenith Satellite System (QZSS). Due to improved solar radiation pressure modeling and other more sophisticated models, the consistency of these products has improved in recent years. The current orbit consistency between different analysis centers is on the level of a few centimeters for GPS, around one decimeter for GLONASS and Galileo, a few decimeters for BeiDou-2, and several decimeters for QZSS. The clock consistency is about 2 cm for GPS, 5 cm for GLONASS and Galileo, and 10 cm for BeiDou-2. In terms of carrier phase modeling error for precise point positioning, the various products exhibit consistencies of 2–3 cm for GPS, 6–14 cm for GLONASS, 3–10 cm for Galileo, and 10–17 cm for BeiDou-2.